Focal and segmental glomerulosclerosis post COVID-19 vaccine - Arellan-Bravo, Luis (2023)
The vaccine against SARS-CoV-2 has demonstrated proven efficacy to control the disease, rare adverse effects due to this therapy are still being studied, some of them renal. It is suggested that an inadequate immune response could be the cause of glomerular diseases associated with vaccination. We describe a 26-year-old patient, with no significant history, received immunity from the SARS-CoV-2 vaccine (Sinopharm), after which he began with proteinuria in the nephrotic range. Proteinuria: 24g in 24 hours. Albumin: 2.36 mg/dl. COVID-19 test negative. Renal biopsy was performed with ultrasound guidance, with anatomopathological result of Focal and Segmental Glomerulosclerosis, tip variant, observing 17 glomeruli. The patient was hospitalized and received immunosuppression with pulses of methylprednisolone, oral prednisone 1mg/kg/day, atorvastatin 20mg/day, antiplatelet therapy with ASA 100mg/day, omeprazole 20mg/day, and trimethoprim-sulfamethoxazole prophylaxis. Two weeks later, the patient had a weight loss (10 kg), the edemas decreased significantly. Four weeks after starting treatment, she presented proteinuria <500 mg/day, which at the moment is within normal values. The development of de Novo focal segmental glomerulosclerosis is possible, after administration of the SARS-CoV-2 vaccine, and that responds to the use of corticosteroids.